Pengaruh kebijakan investasi, dividen, pendanaan dan profitabilitas terhadap nilai perusahaan manufaktur di daftar BEI - Widhian Hardiyanti; Nila Fauziah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Firm value is a value that reflects a fair price paid by an investor in a company. This study focuses on manufacturing companies, because it is seen directly from how far the role of society and other industries in using manufactured products. The purpose of this study is to determine the effect of investment policy, financing policy, and profitability of manufacturing companies listed on the BEI. The method used in this study is a quantitative research method. The sampling technique used is the method of Purposive Random Sampling. This study calculates the profitability ratio with Return on Assets (ROA). Data analysis techniques used are Normality Test, Classical Assumption Test, and Model Test. Tests can say that investment policies do not affect the value of the company. Dividend policy does not affect firm value. The policy does not affect the value of the company. Meanwhile, profitability affects firm value. Companies that experience an increase in profits reflect that the company has a good performance, thus generating positive sentiment from investors and can make the company's price increase.